2014
DOI: 10.1080/01926187.2014.935689
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Improvement in Depression Across Therapies Using Indicators of Romantic Relationship Functioning: A Preliminary Investigation

Abstract: Depression is a common presenting problem, often affected by couple interactions in unique ways. However, research in the area of romantic relationship functioning and depression often replicates previous research or consists of literature reviews, limiting the clinical relevancy. The purpose of this preliminary study is to expand the research on the effects of relational processes on depression treatment outcomes. We tested whether initiator tendency, attachment anxiety, attachment avoidance, and marital sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Based on these findings, addressing issues involving relationship and sexual satisfaction may be a way in which clinicians can help clients assuage depression symptoms. This is consistent with evidence that treatment targeted toward improving the couple's relationship can also treat depression (Denton et al., ; Woods et al., ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on these findings, addressing issues involving relationship and sexual satisfaction may be a way in which clinicians can help clients assuage depression symptoms. This is consistent with evidence that treatment targeted toward improving the couple's relationship can also treat depression (Denton et al., ; Woods et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Particularly, relationship satisfaction was linked with depressive symptoms one year later (e.g., Hollist, Miller, Falceto, & Fernandes, 2007). In addition, preliminary studies of clinical interventions for couples as a way to treat depression suggest early evidence that enhancing a couple's relationship may be linked with positive treatment outcomes for depression (Denton et al, 2012;Woods, Priest, & Denton, 2015).…”
Section: Relationship Satisfaction and Depressive Symptomsmentioning
confidence: 99%
“…However, other studies have produced similar results with regard to explicitly measured attachment anxiety. In the study by Woods and colleagues [35] attachment anxiety did not predict change in depression. McBride and colleagues [18] also found that attachment anxiety was not related to treatment outcome.…”
Section: Discussionmentioning
confidence: 83%
“…Despite this, we were not able to find any research examining the relationship between all three variables—attachment style, relationship satisfaction, and depression—in the same model. This is concerning because common clinical approaches for treating depression in marriage are derived from an attachment framework (Anderson, Beach, & Kaslow, ; Woods, Priest, & Denton, ), yet research has failed to identify clear points of intervention that attempt to change or modify attachment styles in the context of depression. As such, the aim of this study is to use a measure of attachment that focuses more on behaviors—rather than styles—in an effort to explore the pathways between marital satisfaction and depression from an attachment framework.…”
Section: Literature Reviewmentioning
confidence: 99%